Hubungan karakteristik dengan tingkat pengetahuan, sikap dan perilaku bidan puskesmas di Kota Medan tentang pap smear dan kanker serviks - Hilma P. Lubis; Rusli P. Barus; Melvin NG. Barus; Letta S. Lintang; Indra G. Munthe; Sarah Dina (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Objective : To determine the correlation between characteristics and the level of knowledge, attitudes and behavior among midwife in primary health care in Medan about pap smear and cervical cancer.Method : This study was a descriptive analytical with cross sectional design conducted using a 3-sections questionnaire containing 15 knowledge questions, 12 attitude questions, and 8 behavior questions at 100 midwives in 39 primary health care in Medan from October until November 2013. Data was collected by.Data analysis was performed using two way Chi Square with a significance level of 95% (p<0.05).Results : Majority of respondents were good in knowledge (84%), attitude in adequate level (52%), and behavior in good level (52%). In Chi Square analysis, no significant relationship found between educations and knowledge, attitudes, behavior (p=0.184; p=0.417; p=0.185); no significant relationship found between age yet length of working with knowledge, attitudes (p=0.191; p=0.478 and p=0.22; p=0.649) while significant correlation found between age yet length of working with behavior (p=0.003 and p=0.0037).Conclusion : Based on these results, it is shown that better behavior is found in midwife who has an older age and long working age.Keywords : midwife; cervical cancer; pap smear